Analysis of Student Attitudes and Beliefs in Physics Education - Wandi, Wandi; Suwarma, Irma Rahma; Liliawati, Winny; Mardianti, Fani; Amelia, Riski (STKIP Singkawang, 2024)
Understanding the attitudes and beliefs of physics students is a critical step in overcoming obstacles and creating a more positive and conducive learning environment. To achieve that aim, the study is strategically designed to achieve the following objectives: 1. to compare student attitudes and beliefs about learning physics to the perspectives of experts in the field; and 2. to investigate disparities in student attitudes and beliefs about gender, with the goal of identifying potential gender-based variations that could impact problem-solving performance in the field. We used a quantitative descriptive study approach to comprehensively explore high school students' attitudes and beliefs about physics, as well as to compare their viewpoints with those of professionals in the area. We're using the Colorado Learning Attitudes about Science Survey (CLASS). The findings show that the majority of pupils had scores between 50 and 60, suggesting a modest level of conformity to the expert. In terms of gender, female pupils clearly surpass their male counterparts. While both male and female students excel in courses that correlate with their own interests, they experience similar obstacles in learning applied conceptual knowledge. These findings emphasize the necessity of targeted treatments and educational techniques for addressing inequities and promoting overall academic success in children of both genders.